To Study the Effects of Environment and Different Soil Mixture on Germination of Acacia nilotica Seed at Nursery Stage - Bahuguna, V. K.; Lal, Pyare (Indian Forester, 1990)
This paper presents the results of an investigation carried out for producing healthy seedlings of Acacia nilotica species in nursery. The results revealed that the combination of direct sowing in ploybags or sowing in boxes with a soil media consisting of soil and sand in 2: 1 ratio gave best results upto germination. After germination for better growth of the seedlings Farm Yard Manure sbould be added in the ratio 2: 1 : 1 (Soil: Sand: F.Y.M.).